A Historical Overview on Coronary Surgery and Interventional Cardiology: Parallel Pathways? - Bonacchi, Massimo; Maiani, Massimo; Conti, Andrea A. (Vascular Disease Prevention (Discontinued), 2006)
Coronary surgery includes the majority of cardiac surgery interventions in industrialised countries and represents the most common complex surgery in the world with a trend towards an increase. Every year approximately 800,000 patients worldwide undergo Coronary Artery By-pass Grafting (CABG) with a peri-operative mortality of 1-3%. Over the years, the indications for CABG have changed and remain in continuous evolution not only because of the development of innovative diagnostic and surgical techniques, but also because of the introduction of new non-surgical strategies that can manage cases that in the past were referred to cardiac surgeons. A notable example of this is the Percutaneous Coronary Interventions (PCI), and the subsequent introduction of always more sophisticated stents, which have substantially contributed to the modification of the population of patients undergoing CABG. As a result, patients undergoing cardiac surgery are increasingly aged and with more serious coronary artery involvement. For these reasons, the mean surgical risk expected for cardiac surgical patients has increased in recent years. This review summarises the developments in coronary surgery, tracing a parallel with interventional cardiology and provides a vision of future trends.
Keywords: percutaneous coronary intervention